MAXIMIZING MANAGEMENT AND UTILIZATION OF VILLAGE CASH LAND AND LAND OF PELUNGGUH WARD GUWOSARI PAJANGAN - Riyanto; Adji Suradji Muhammad (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This research is entitled "Maximizing the Management and Utilization of Village Treasury Land and Plungguh Land in Guwosari Pajangan Subdistrict." This research aims to find out how to optimize the management of the village treasury and pelungguh land rentals managed by the Village Head in Bantul Regency, solving problems in managing lunch land rentals by the Village Head. His party will also determine what efforts are being made to overcome problems related to land rental by the village head in Guwosari Village (Bantul Regency). This research uses empirical methods focusing on facts in the field; secondary data support primary data. The data obtained from respondents and resource persons will be analyzed qualitatively. This research concludes that optimizing the management of Pelungguh land rentals is quite good, even though there are obstacles in its management